Risk factors for jockey falls in Japanese thoroughbred flat racing - Mizobe, F.; Takahashi, Y.; Kusano, K. (Journal of Equine Veterinary Science, 2021)
Jockey safety is of paramount importance from welfare perspective and public perception. This retrospective case-control study aims to identify risk factors associated with jockey falls (JF) in flat races of Japan Racing Association (JRA). JF in 715,210 race starts by 74,328 horses at 10 racecourses from 2003 to 2017 were reviewed. Data were extracted from a database maintained by JRA and from official accident reports issued by race stewards. Seventeen possible risk factors were evaluated using multivariable logistic regression, to identify those significantly associated with JF. A total of 992 JF incidents were recorded, with an incidence rate of 1.39 falls per 1,000 starts (95% CI: 1.30-1.48). 6 risk factors were significantly associated with JF. Odds increased with horses that sustained catastrophic musculoskeletal injury (CMI) (OR: 203; CI: 169-241; P < 0.001). Increased odds were also associated with dirt track surfaces (OR: 1.99; CI: 1.74-2.29; P < 0.001), apprentice jockeys (OR: 1.43; CI: 1.21-1.68; P < 0.001), smaller track sizes (OR: 1.41; CI: 1.24-1.61; P < 0.001), larger fields (OR: 1.25; CI: 1.07-1.47; P = 0.005), and longer race distances (OR per 200 m: 1.05; CI: 1.01-1.09; P = 0.02). Since CMI was identified as a major contributing factor for JF, measures to minimize CMI may lead to improvement of jockey safety. The increased odds associated with apprentice jockeys may indicate the importance of jockey education and training. For jockey safety, proper staffing of medical professionals especially for races on dirt, smaller track, larger fields, and longer distances is recommended.